How do early socioeconomic circumstances impact inflammatory trajectories? Findings from Generation XXI - Soares, S (2020)
Background: The association between socioeconomic position and markers of inflammation in adults, including C-reactive protein (CRP), is well-established. We hypothesized that children from families of less-advantaged socioeconomic circumstances may be at higher inflammatory risk during childhood and, consequently, throughout their life course. Thus, we aimed to investigate whether early socioeconomic circumstances impact CRP trajectories using repeated measures of data from a population-based birth cohort. Methods: Data from 2510 participants of Generation XXI, a prospective Portuguese population-based birth cohort, were included in this study. Early socioeconomic circumstances comprised maternal education and occupation, paternal education and occupation, and household income at the child’s birth. Venous blood samples were collected from the children at ages four, seven, and ten years, and high-sensitivity CRP (Hs-CRP) was quantified. Hs-CRP trajectories were computed using a linear mixed-model approach. Results: Participants from less-advantaged socioeconomic circumstances presented higher levels of Hs-CRP by age of ten years. The higher the mother´s education and disposable household income, the lower the minimum value of the log Hs-CRP observed throughout childhood. Further, the age at which that minimum log Hs-CRP value was reached occurs later, meaning that children born in more-advantaged socioeconomic circumstances had lower levels of log Hs-CRP compared with children from less-advantaged families. Conclusions: Poor socioeconomic circumstances early in life are associated with increased inflammation levels throughout the first decade of life. This study demonstrates that social inequalities may impact population health beginning at very early ages.